IL-4 and interferon-gamma production in children with atopic disease. - Tang, M (1993)
In vitro studies have implicated reciprocal roles for IL-4 and interferon-gamma (IFN-gamma) in the regulation of IgE production. As elevated IgE is a major feature of atopic disease, an important question is whether an imbalance of IL-4 and IFN-gamma is present in vivo. The production of IL-4 and IFN-gamma in phytohaemagglutinin (PHA)-stimulated peripheral blood mononuclear cell cultures from atopic children was examined to determine if there is an increased production of IL-4 and/or a reduced production of IFN-gamma. Highly atopic children with IgE > 600 U/ml produced significantly more IL-4 and less IFN-gamma in vitro than age-matched non-atopic controls. Production of IL-4 and IFN-gamma in mildly atopic children was equivalent to controls. These findings indicate that highly atopic children have an imbalance of IL-4 and IFN-gamma production and that the degree of imbalance relates to severity of the atopic state. The ratio of in vitro IL-4: IFN-gamma production correlated positively with serum IgE, which suggests that the balance of these two cytokines is a factor in the regulation of IgE, in vivo. It remains to be determined whether this imbalance of IL-4 and IFN-gamma in the highly atopic children is the cause or result of the disease process.